The accuracy of the Manchester Triage System in an emergency service - Jaqueline Pereira da Costa; Rafael Nicolaidis; Ana Valeria Furquim Gonçalves; Emiliane Nogueira de Souza; Carine Raquel Blatt
ABSTRACT Objective: To verify the accuracy of the Manchester Triage System (MTS) and the outcomes of adult patients in an emergency hospital service. Method: Cross-sectional study, conducted through an inspection of records of risk classification of adult patients treated in the emergency service of a hospital. Results: The patients (n = 400) were classified according to priority levels, in red (0.8%), orange (58.2%), and yellow (41.0%). The accuracy levels between auditors and nurses were substantial for the flowchart (K = 0.75), and moderate for discriminating factors (k = 0.46) and priority levels (k = 0.42). The accuracy of the MTS was 68.8% with regard to priority levels. Regarding outcomes, 60% of patients were discharged, 37% were transferred to other units, and 3% died. Conclusion: The MTS proved to be a good predictor of the assessed outcomes, showing that 65.9% of Low Urgency patients progress to discharges, and 3.8% of High Urgency patients progress to death. The accuracy of the MTS was moderate, which suggests the need to implement inspections in emergency services.